Transformasi Sosial Politik Kaum Santri Di Lombok - Rahman, Lalu Muhamad Fazlur (Sophist : Jurnal Sosial Politik Kajian Islam dan Tafsir, 2023)
The word “Lombok” has a philosophical meaning which in Sasak means straight. In a different perspective it will give a broad meaning as well as become a spirit in every side of the life of the Lombok people starting from the interaction of the community both inside and with the outside world, this can be seen from the meaning of the word Lombok which means straight in their interactions who firmly hold good values ​​towards others, because straight is the opposite of crooked which has a negative connotation, this factor then shapes the character of the Lombok people so that they are known as people who are polite, friendly and firm in maintaining principles. Likewise, from a religious point of view, firmness in upholding religious teachings which contain good values ​​is reflected in the high respect for the characters, whether Tuan Guru, Ustadz, Guru or santri in general, which is manifested from their influence by religious leaders in carry out social and political changes in society. Researchers try to examine this reality using library research method so that they can find out the dynamics that occur with accurate data and understand the extent of the role of the santri in carrying out socio-political changes in Lombok society. Keyword: Lombok, Political Culture, Santri, Social Transformation